Synthesis of magnetorheological fluid and its application in a twin-tube valve mode automotive damper. (July 2020) - Madhavrao Desai, Rangaraj; Acharya, Subash; Jamadar, Mohibb-e-Hussain; Kumar, Hemantha; Joladarashi, Sharnappa; Sekaran, SC Raja
The change in rheological properties of smart materials like magnetorheological fluid when brought under the influence of a magnetic field can be utilized to develop magnetorheological devices where the output has to be continuously and quickly varied using electronic control interface. In the present study, magnetorheological fluid is synthesized and used as a smart fluid in a twin-tube magnetorheological damper operating in valve mode. The behavior of the magnetorheological fluid is experimentally characterized in a rheometer and mathematically modeled using Herschel–Bulkley model. The parameters of the Herschel–Bulkley model are expressed as polynomial functions of strength of the magnetic field in order to find the shear stress developed by the magnetorheological fluid at any given strength of the magnetic field applied. The magnetorheological damper, which was designed for application in a passenger van, is tested in the damper testing machine. The performance of the damper at different damper velocities and current supplied is studied. The range of values for the parameters of the experimental testing are chosen to emulate the actual conditions of operation in its intended application. Nondimensional analysis is performed, which links magnetorheological fluid rheological properties and geometrical parameters of magnetorheological damper design with the force developed by the damper. Finite element method magnetics is used to find the strength of the magnetic field at the fluid flow gap. Analytical methods are used to calculate the damper force developed due to the field-dependent yield stress and compared with experimental force values. The resulting dynamic range of the magnetorheological damper is also assessed.